Examining the role of education in the social inclusion of Syrian refugees in Turkish middle schools - Jusufbasic, Seherzada (My University, 2019)
Bu nitel çalışma, Suriyeli mülteci çocukların Türkiye'deki devlet okullarına sosyal uyumunu incelenmesi amaçlanmıştır. Bu doğrultuda araştırmamızda aşağıdakileri belirlemek üzere, 20 öğretmen, 9 rehber oğretmen, 54 Süriyeli ve 53 Türk öğrencinin görüşleri alınmıştır: Türkiye'deki mülteci kökenli öğrenciler için okul deneyimleri nelerdir ve politika ile uygulama bu deneyimleri nasıl etkilemektedir; yeni bir eğitimin mülteci çocukların yaşamları üzerindeki “etkileri” nelerdi; mülteci çocuklarla doğrudan temas halinde olan öğretmen ve okul danışmanlarının sosyal uyum hakkındaki görüşleri nelerdir; Suriyeli ve Türk çocukların yeni çok kültürlü çevre konusundaki hisleri ve tutumları nelerdir?Bire bir yarı-yapılandırılmış görüşmeler ve odak grupları veri toplama yöntemleri olarak kullanılmıştır. Araştırma, İstanbul'da Küçükçekmece, Bağcılar ve Esenyurt ilçelerinde 10 ortaokulda yürütülmüştür. Araştırma sonucunda, Suriyeli öğrencilerin Türk devlet okullarındaki zorlukları: dil engeli, kültürel farklılıklar, önceki eğitim eksikliği, sosyo-ekonomik faktör, davranış sorunları ve ebeveynlerin ilgisizliği olduğunu sonucuna ulaşılmıştır. Ayrıca, mülteci çocuklar ve çevre arasındaki ilişkilerin okula ve topluma başarılı sosyal katılımda çok önemli bir role sahip olduğunu göstermektedir. Okullarda çok kültürlü bir ortamı teşvik etmek ve mülteci eğitimi için okul personelini eğitmek, mülteci kökenli öğrencilerin okullara sosyal olarak dahil edilmesini geliştirmek için önemli önerilerden bazılarıdır.

The purpose of this qualitative study is to examine the social inclusion of Syrian refugee children in Turkish public schools. Accordingly, this investigation sought the views of 20 teachers, 9 school counselors, 54 Syrian and 53 Turkish children, in order to answer the following research questions: firstly, what are the experiences of school for students with a refugee background in Turkey, and how do policy and practice intersect to affect these experiences; secondly, what are the “effects” of this new education on the lives of refugee children; thirdly, what are the opinions of teachers and school counselors that are in direct contact with refugee children about their social inclusion; and, lastly, what are the feelings and attitudes of Syrian and Turkish children about this new multicultural environment?One-on-one semi-structured interviews and focus groups were the methods of data collection. The research was conducted in 10 middle schools in the districts of Küçükçekmece, Bağcılar, and Esenyurt in Istanbul. The findings of the research have revealed that the common hardships of Syrian students in Turkish public schools are: the language barrier, cultural differences, lack of prior education, socio-economic factors, behavioral problems, and parents' indifference. Moreover, the environment's influence has a crucial role in the successful social inclusion of refugee children in both schools and the host society. Supporting a multicultural climate in schools and the training of school staff to ensure a better education of refugee children are some of the major recommendations for improving the social inclusion of refugee-background students in Turkish schools.
Keywords: Education; Eğitim; İstanbul; İstanbul Syrian refugee students; mülteci eğitimi; refugee education; social inclusion; sosyal uyum; Süriyeli mülteci öğrenciler